Integrated effects of temperature and COD/N on an up-flow anaerobic filter-biological aerated filter: Performance, biofilm characteristics and microbial community. (December 2019) - Zhou, Hexi; Xu, Guoren
Graphical abstract: Highlights: The integrated effects of temperature and COD/N ratio on UAF-BAF were studied. The biofilm physicochemical characteristics were related to operational parameters. The total cells and EPS of biofilm structure were characterized by CLSM. Temperature and COD/N ratio shaped the microbial community of UAF-BAFs. The functional potential was responsible for the performance of system. Abstract: The integrated effects of temperature and COD/N ratio on performance, biofilm characteristics and microbial community in up-flow anaerobic filter-biological aerated filters (UAF-BAFs) were investigated. Results indicated that the UAF-BAF system could achieve excellent COD, NH4 + -N and TN removal, in which effluent quality well met the Class 1A standard. Biofilm physicochemical characteristics showed that the biomass, biofilm thickness and extracellular polymeric substance (EPS) content in the UAF-BAFs reduced with the decrease in COD/N ratio, but were enhanced under low temperature. The biofilm structure characterized by CLSM in the UAF-BAFs significantly shifted, which was closely correlated with operational conditions. Sequencing analysis revealed that Proteobacteria, Epsilonbacteraeota, Bacteroidetes and Firmicutes were dominant in the UAFs and the abundance of ammonium oxidizing bacteria (AOB) was responsible for nitrification performance in the BAFs. Functions analysis indicated that amino acid metabolism, carbohydrate metabolism, energy metabolism and lipid metabolism were clearly regulated by parameters changes.